Creating Spaces of Music Asylum in Ethnically Divided Contexts: Young People's Accounts from Bosnia and Herzegovina and Sri Lanka. Issue 1 (1st June 2022) - Howell, Gillian; Korum, Solveig
Abstract: This article explores the ways in which arts experiences in conflicted and territorialized settings may invite a heightened engagement with space, and what this suggests about creative experiences as a vehicle for transforming space and the (re)construction of one's presence and place in the world. Presenting ethnographic data from two youth music projects established after the wars in Bosnia and Herzegovina and Sri Lanka and argued from the perspective of musician-practitioner-researchers, the authors examine how musical interaction, improvisation, and performance creation enabled processes of exploring, reconfiguring, and expanding the participants' identities and sense of place in the surrounding world. Using Tia DeNora's conceptualization of "music asylum, " the article shows how strategies of removal and refurnishing created creative and safe spaces in which alternative lives and more complex identities could be rehearsed and conflict narratives could be revised, fostering a temporary transformation of space that is captured in metaphors like bubble, refuge, and sanctuary.